A Co3O4/MnCO3 heterojunction on three-dimensional nickel foam for an enhanced oxygen evolution reaction. Issue 23 (27th May 2020) - Yang, Guijin; Zhu, Botao; Gao, Daqiang; Fu, Yujun; Zhao, Jing; Li, Jinyun
Abstract : A Co3 O4 /MnCO3 heterojunction on NF with a unique architecture exhibits prominent OER activity and stability that is superior to most Co3 O4 -based catalysts. Abstract : For water electrolysis and metal–air batteries, the rational design and preparation of highly efficient and environmentally friendly catalysts for the oxygen evolution reaction (OER) is urgently required. Here, abundant Co3 O4 /MnCO3 heterointerfaces supported on Ni foam are facilely fabricated via an energy-efficient hydrothermal annealing method. The heterostructure and cactus-like hierarchical structure enable the sample to have prominent OER activity and excellent stability. Specifically, the electrocatalyst requires only a low overpotential of 273 mV at a current density of 10 mA cm −2 and has a small Tafel slope of 62.06 mV dec −1 in 1 M KOH electrolyte; these results are superior to most non-noble metal based OER catalysts reported to date. Our work provides a novel perspective for the rational design and synthesis of low-cost electrocatalysts, especially in the selection of other low-budget compounds for interface engineering.